The Influence of Corporate Social Responsibility (CSR) and Environmental Management Accountng on Sustainable Hotel Performance in Bandung Regency - SARI, Kadek Ayu Kristina Indah; SAPUTRA, Komang Adi Kurniawan; KAWISANA, Putu Gede Wisnu Permana (Journal Management and Hospitality, 2023)
The hotel industry is one of the sectors operating in the service industry. The increasing number of hotels year after year has resulted in tighter and more intense competition. This growing competition drives hotel management to find solutions to enhance their competitiveness. This study aims to determine the influence of Corporate Social Responsibility (CSR) and Environmental Management Accounting on the sustainable performance of hotels in Badung Regency. The sample used in this study consists of 130 hotels in Badung Regency, employing a saturated sampling technique. All data obtained from the distribution of questionnaires were deemed suitable for use and were subsequently analyzed using multiple linear regression. The results indicate that Corporate Social Responsibility partially affects sustainable performance variables. Environmental management also has a partial effect on sustainable performance variables. Both Corporate Social Responsibility and environmental management simultaneously affect sustainable performance.